Reboisasi Sebagai Upaya Konservasi Dan Pelestarian Air Di Desa Balesari - Widihastuti, Rahma Ari (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2024)
Global warming is currently a natural problem by all levels of society in the world. One sign of global warming is a rise in temperature in the air. The cause of global warming is from humans themselves such as the use of fossil fuels. One of the efforts to save the earth from global warming can be by reforestation. Through reforestation activities can restore the function of forests, namely as the lungs of the world. In order to protect the natural environment on Mount Giyanti located in Balesari Village, Windusari District, Magelang Regency, Central Java. Through UNNES GIAT 5 KKN (Real Work Lecture) activities, the author carried out one of the work programs, namely reforestation on Mount Giyanti. This is also a manifestation of community service, especially in Balesari Village. The method used is first preparation and then second implementation of activities. Through reforestation activities, it is expected to help global warming that hit the world.